The Dual Role of Gentamicin in Gene Expression of Fibronectin Binding Proteins in Staphylococcus Aureus - Hind Tahseen Ibrahim (Journal of Global Pharma Technology, 2018)
Objectives: The current work aimed to reveal the impact of gentamicin on the fibronectin binding proteins (fnbp) gene expression and its relation to biofilm and agr type in Staphylococcus aureus.  Materials and Methods: A total of 25 S. aureus isolates were enrolled in this study previously isolated from different specimens. Identification confirmation and methicillin resistance were achieved by amplification of 16SrRNA and mecA. Multiplex polymerase chain reaction (PCR) based assay was employed to evaluate the agr typing. The gene expression of fnbA and fnbB genes was tested by real-time PCR technique. Minimum inhibitory concentration was estimated by micro broth dilution methodology. Microtiter plate method was performed to determine the adhesiveness of to human fibronectin, with and without gentamicin. Results: Here we revealed a weak inverse correlation was observed between gene expression of either fnbA or fnbB with each of biofilm forming capacity and agr type. Whereas there was a strong correlation between fnbA and fnbB gene expression. Furthermore, gentamicin affected the bacterial genome in a way that down-regulates one of the genes in question; meanwhile, up-regulates the other one. Moreover, the current study found that polysaccharides production in 48% of isolates significantly (P<0.05) reduced by increasing fibronectin concentration. Conclusion: gentamicin has dual impacts on fnb genes expression. Albeit much work is needed; however, it is strongly suggested that gentamicin should be omitted from antibiotic regimen in treating S. aureus isolates.Keywords: Gentamicin, Fnba, Fnbb, Biofilm, Staphylococcus arueus.